Beclin1 Deficiency Suppresses Epileptic Seizures - Yang, Min; Lin, Peijia; Jing, Wei; Guo, Haokun; Chen, Hongnian; Chen, Yuanyuan; Guo, Yi; Gu, Yixue; He, Miaoqing; Wu, Junhong; Jiang, Xuejun; Zou, Zhen; et al. (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a common disease of the nervous system. Autophagy is a degradation process involved in epilepsy, and in turn, seizures can activate autophagy. As a critical role in autophagy, Beclin1 participates in numerous physiological and pathological processes. However, how Beclin1 influences epilepsy remains unclear. In this study, we detected increased expression of Beclin1 in brain tissues from patients with temporal lobe epilepsy. And heterozygous disruption of beclin1 decreased susceptibility to epilepsy, suppressed seizure activity in two mouse epileptic models. We further illustrated for the first time that heterozygous disruption of beclin1 suppresses excitatory synaptic transmission, which may be caused by the decreased dendritic spine density. These findings provide a new clue that the regulation of Beclin1, may serve as a strategy for antiepileptic therapy. Besides, Beclin1 participates in synaptic transmission, and the development of dendritic spines may be a biological function independent of autophagy.